Construction technologies and mechanical effects of the pipe-jacking crossing anchor-cable group in soft stratum - Han, Jianyong; Wang, Jun; Jia, Dongfeng; Yan, Fushun; Zhao, Yue; Bai, Xiaoyu; Yan, Nan; Yang, Guang; Liu, Dong (Frontiers in Earth Science, 2023)
Ordinary pipe-jacking equipment cannot cross areas with existing anchor cables in soft stratum remains a issue, a construction technology that uses steel sheet pile + jet grouting pile for waterproof and open cut method to cross the anchor cable area was proposed. The case history of the pipe jacking project of sewage treatment plant at Jinan East Railway Station Area was studied. The mechanical properties of steel sheet piles, the horizontal displacement of piles and the ground surface settlement in the anchor cable crossing area was investigated based on the in-situ observations. Numerical investigations were performed using the finite element method. The effect of existing anchor cables on the mechanical behaviors of retaining structures, deformation variation of the ground and stability of the excavation were revealed. The results show that the combination supporting structure of steel sheet pile and jet grouting pile has a good effect on the waterproof and deformation control in areas with existing anchor cables. When the steel sheet pile touches the anchor cable during the pile jacking, the compressive stress at the pile cap increases rapidly until it reaches 62.8 MPa (the maximum pressure provided by the pile pressing machine), which is twice as the pressure at ordinary condition. Maximum horizontal displacement of retaining pile δv approximately increases linearly with the excavation depth He. The existing anchor structures behind the excavation can restrain the deformation of ground and retaining structure to a certain extent. The δv value of the pile with the existing anchor structures behind is 6.5 mm, approximately 0.01 % of the He value, which is 70 % of that of the retaining pile without existing anchor structures. The ground surface settlements on both sides of the excavation are in "groove type". The maximum ground settlements δh are 0.29 % He and 0.05 % He , respectively. The plastic zone at both sides of the excavation bottom extends to the ground surface with an angle of about 45°. The plastic zone range in the ground with existing anchor cables when excavation fails is significantly larger than that in the ground without anchor cables.